Peran Kepala Sekolah dalam Membangun Citra Publik pada Era 5.0 di Kabupaten Banyuwangi - Slamet (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
This study aims to determine the role of the principal in building a public image, to know the strategis steps taken by the principal and to find out the problems and solutions taken in building public cintra at SMK NU Darussalam, Srono District. The method used in this study is a qualitative method. The data collection techniques used are observation, interviews and documentation. The data analysis used is interactive analysis. The results of the research conducted are; Petama, SMK NU Darussalam, Srono District, has a very good and positive image in the eyes of the public. This can be seen from the many participations of the community who are willing to send their children to school at SMK NU Darussalam, Srono District, even though they are still new schools. Second, in taking the decision of the principal, always be firm and think openly, the thing that is no less important is that before finally taking a decision, the principal of SMK NU Darussalam, Srono District, conducts deliberations to find consensus so that the decisions taken do not reap conflicts, especially internal conflicts. Third, in general, the problems faced by SMK NU Darussalam Srono District are facilities and infrastructure and facilities that are still minimal, besides that there are still some teachers who are still pessimistic about other schools. Some solutions that must be done are that the principal gives motivation to teachers to continue to take a humanist approach to the surrounding community in the hope that the community will be more convinced that SMK NU Darussalam Srono District is the right choice.